Critical Organ Dysfunction and Preoperative Mortality in Newborns with Hypoplastic Left Heart Syndrome - Durbin, Matthew D.; Wynn, James L.; Chaudhry, Paulomi; Posorske, Alyx; Voskoboynik, Ellen; Park, Woo Y.; Lavilla, Orlyn; Aziz, Khyzer B. (American Journal of Perinatology, 2024)
Hypoplastic left heart syndrome (HLHS) is fatal without surgical intervention. An important subset of HLHS patients die prior to surgical intervention, but this population is underevaluated. The neonatal sequential organ failure assessment score (nSOFA) is an operational definition of organ dysfunction that can identify those with a high risk of mortality among neonatal intensive care unit (NICU) patients. The utility of the nSOFA to predict preoperative mortality in the unique HLHS population is unknown and could inform care, particularly care provided by neonatology staff. We performed a multicenter retrospective cohort study of HLHS cases across three level IV NICUs from January 1, 2009, to December 3, 2023. Patients were classified as either survived or died prior to surgical intervention. Demographic variables were curated from medical records including the maximum nSOFA (nSOFAmax) before surgical intervention or death. We identified 265 patients with HLHS over the study period. The nSOFAmax was greater in patients who died preoperatively (14/265; 5%) compared with survivors to surgical intervention (median 8 [interquartile range, 6, 12] vs. 2 [0, 4]; p < 0.001). The area under receiver operating characteristics curve for the nSOFAmax to discriminate for mortality was 0.93 (95% confidence interval, 0.88–0.98; p < 0.001). Compared with an nSOFAmax of 0, the likelihood ratio for preoperative death doubled at 2, tripled at 4, and was 10-fold at 9. This is the first demonstration of nSOFA utility in specific to congenital heart disease and HLHS. The nSOFAmax represents a novel, electronic health record-compatible, and generalizable method to identify patient-level organ dysfunction and risk for preoperative mortality in HLHS patients.Key Points
Keywords: congenital heart disease; hypoplastic left heart syndrome; illness severity score; nSOFA score